Synthesis Of 2-Benzoyl-3,4,5,6-Tetrasubstitutedbenzoic Acid From Tetrasubstituted Phthalic Anhydride Using Organometalics (Journal of the Bangladesh Chemical Society, 2013)
The reactions of phenylcoppermagnesium and phenylmagnesium bromide reagents with perchlorophthalic anhydride were investigated. Along with 2-benzoyl-3,4,5,6- tetrachlorobenzoic acid, five other substituted products were isolated and their structure were determined by detailed spectroscopic studies. Journal of Bangladesh Chemical Society, Vol. 25(2), 186-193, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15085